2020
DOI: 10.1111/pala.12492
|View full text |Cite
|
Sign up to set email alerts
|

Formation binning: a new method for increased temporal resolution in regional studies, applied to the Late Cretaceous dinosaur fossil record of North America

Abstract: The advent of palaeontological occurrence databases has allowed for detailed reconstruction and analyses of species richness through deep time. While a substantial literature has evolved ensuring that taxa are fairly counted within and between different time periods, how time itself is divided has received less attention. Stage-level or equalinterval age bins have frequently been used for regional and global studies in vertebrate palaeontology. However, when assessing diversity at a regional scale, these resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 101 publications
1
36
0
1
Order By: Relevance
“…Nevertheless, even among these broadly consilient results, differences in reported pattern still require investigation. For example, Brusatte et al [3] and Dean et al [28] rejected a global long-term decline prior to the K-Pg boundary but found evidence for declines in species-richness and disparity at the end of the Cretaceous, Lloyd [30] found a long-term decline in sauropod and ornithischian diversity through the Cretaceous, and Barrett et al [12] recovered evidence for negative trends in theropod and ornithischian diversity during the last two stages of the Cretaceous but identified a radiation of Late Cretaceous sauropodomorphs. These differing results highlight the need to increase the density and spatio-temporal scope of taxon sampling for these clades and to combine detailed, stratigraphically controlled, regional-level analyses to provide a truly holistic picture of the biotic changes that occurred during this critical interval.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, even among these broadly consilient results, differences in reported pattern still require investigation. For example, Brusatte et al [3] and Dean et al [28] rejected a global long-term decline prior to the K-Pg boundary but found evidence for declines in species-richness and disparity at the end of the Cretaceous, Lloyd [30] found a long-term decline in sauropod and ornithischian diversity through the Cretaceous, and Barrett et al [12] recovered evidence for negative trends in theropod and ornithischian diversity during the last two stages of the Cretaceous but identified a radiation of Late Cretaceous sauropodomorphs. These differing results highlight the need to increase the density and spatio-temporal scope of taxon sampling for these clades and to combine detailed, stratigraphically controlled, regional-level analyses to provide a truly holistic picture of the biotic changes that occurred during this critical interval.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Brusatte et al . [ 3 ] and Dean et al [ 28 ] rejected a global long-term decline prior to the K-Pg boundary but found evidence for declines in species-richness and disparity at the end of the Cretaceous, Lloyd [ 30 ] found a long-term decline in sauropod and ornithischian diversity through the Cretaceous, and Barrett et al . [ 12 ] recovered evidence for negative trends in theropod and ornithischian diversity during the last two stages of the Cretaceous but identified a radiation of Late Cretaceous sauropodomorphs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, due to an insufficient amount of comparative data within high‐resolution time bins (Dean et al . 2020) and the inherent errors in radiometric dating (Gates et al . 2010), the creation of a more tightly constrained correlative window is presently impractical.…”
Section: Methodsmentioning
confidence: 99%
“…2016; Dean et al . 2020). Currently, the Upper Cretaceous Hell Creek Formation, a fossil‐rich package of terrestrial sedimentary rocks associated with the retreat of the epicontinental Western Interior Seaway (WIS), provides the only well‐constrained evidence for community–environment relationships in the broader context of palaeogeography, floral zonation, palaeoclimate and sea‐level changes (Brusatte et al .…”
Section: Concept Descriptionmentioning
confidence: 99%